Review of the fossil record of Bittacomorphinae (Diptera: Ptychopteridae) - Lukashevich, Elena D. (Zootaxa, 2019)
The fossil record of Bittacomorphinae is poor. The two extant bittacomorphine genera are unknown as fossils and only two extinct genera, each with two species, have been described earlier: Zhiganka Lukashevich, 1995 from the Mesozoic of Eurasia and Probittacomorpha Freiwald et Willmann, 1992 from the Cenozoic of Europe. Both previously known species of Zhiganka have each been described based on a single isolated wing. A discovery of well preserved complete males and females of Zhiganka longialata sp. nov. from Khasurty (Western Transbaikalia, Russia) makes the diagnosis of Bittacomorphinae more vague, but does not contradict the bittacomorphine affinity of Zhiganka and confirms the Early Cretaceous age of the subfamily.